SINGKATAN DAN AKRONIM DALAM ACARA INDONESIA LAWAK KLUB DI TRANS 7 (Abbreviation and Acronym of Indonesia Lawak Klub in Trans7) - Rahmatiah Rahmatiah (Balai Bahasa Sulawesi Selatan, 2014)
Abbreviation and acronym are one way to communicate effectively. One of abbreviation and acronymdevelopments is found in Indonesia Lawak Klub program in Trans7. Abbreviation and acronym become theprocess of word formation in Indonesian language. The writing’s objective is to describe acronym found inIndonesia LawakKlub. It applies descriptive qualitative method with listening-noting technique and libraryresearch. After analyzing it, it finds out form and meaning of abbreviation and acronym. Acronym undergoinggeneralization of meaning could connote better than the previous one or conversely.